2004
DOI: 10.1111/j.1399-3038.2004.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Aeroallergen sensitization in pediatric allergic rhinitis in Singapore: Is air‐conditioning a factor in the tropics?

Abstract: Singapore is a unique blend of a tropical environment with a high standard of hygiene and public health care. The objective was to define the prevalence, clinical characteristics, and environmental risk factors of specific aeroallergen sensitization in pediatric allergic rhinitis patients in this unique environment. The method adopted was a retrospective analysis of allergic rhinitis patients, undergoing aeroallergen skin prick testing (SPT), in the outpatient specialty clinic of the KK Children's hospital, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
(25 reference statements)
2
27
0
3
Order By: Relevance
“…None of the three reported for allergic sensitization. In the rhinitis case series from Singapore, there was no association between cat or dog ownership and sensitization to the pet [26]. Again, these studies have shown inconsistent results for cat ownership, with fewer results but more consistency for dog ownership.…”
Section: Cross-sectional Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…None of the three reported for allergic sensitization. In the rhinitis case series from Singapore, there was no association between cat or dog ownership and sensitization to the pet [26]. Again, these studies have shown inconsistent results for cat ownership, with fewer results but more consistency for dog ownership.…”
Section: Cross-sectional Studiesmentioning
confidence: 93%
“…For allergic sensitization, no study found an increase in risk with pet owners, but the patterns of pet ownership associated with a decrease were varied (cats [14], dogs [16], and any feathered or furred pet [17]). Table 3 summarizes asthma case-control studies and asthma case-only studies [19][20][21][22][23][24][25][26]. For the two asthma/ rhinitis case-control studies, there was a decrease in the risk for sensitization to cat with higher Fel d 1 levels [20,21] or cat ownership [22].…”
Section: Cross-sectional Studiesmentioning
confidence: 95%
“…Differences in the rate of positive SPT can be due to various factors such as number of allergens tested, climatic region and age of patients. With regard to optimum growing conditions, including high humidity for molds (28,29), Unexpectedly, this particular allergy was also found in hot and dry regions, like Saudi Arabia (6) and Kuwait (9,30), It might be associated with increasing the use of air conditioners inside the houses which make good environment for molds to grow and increase exposure to their allergens (26,28).…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of sensitization to molds are found in tropical countries like Singapore and Malaysia (26,27). In a study on 85 patients with allergic rhinitis, in Malaysia, prevalence of allergy to Alternaria and Aspergillus were 12.9% and 12.2%, respectively (27).…”
Section: Discussionmentioning
confidence: 99%
“…Indoor dampness and mold in children's bedrooms were important risk factors associated with allergic symptoms in young children in Singapore [4]. Also, mold sensitization was signifi cantly more common in children whose Singapore homes lacked air conditioning [5]. The objective of this study was to assess the mold growth in Singapore shopping centers using a DNA-based method of mold analysis called mold-specifi c quantitative PCR (MSQPCR) [6].…”
Section: Introductionmentioning
confidence: 99%